2010
DOI: 10.1370/afm.1169
|View full text |Cite
|
Sign up to set email alerts
|

Field Test Results of a New Ambulatory Care Medication Error and Adverse Drug Event Reporting System--MEADERS

Abstract: PURPOSE In this study, we developed and fi eld tested the Medication Error and Adverse Drug Event Reporting System (MEADERS)-an easy-to-use, Web-based reporting system designed for busy offi ce practices. METHODSWe conducted a 10-week fi eld test of MEADERS in which 220 physicians and offi ce staff from 24 practices reported medication errors and adverse drug events they observed during usual clinical care. The main outcomes were (1) use and acceptability of MEADERS measured with a postreporting survey and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 15 publications
4
53
2
5
Order By: Relevance
“…1 Others have demonstrated that errorand event-reporting systems can be implemented in primary care; however, these rarely focus on near misses or the coordination of near-miss reports with quality improvement (QI). [2][3][4][5][6][7][8][9] Barriers to reporting events include the additional workload burden, concern over punitive action, lack of confidence that positive change will result, and psychological barriers to admitting an error. 10 -14 Anonymous reporting systems may increase the number of error reports and reduce concerns about punitive actions but might reduce the detail of the events.…”
mentioning
confidence: 99%
“…1 Others have demonstrated that errorand event-reporting systems can be implemented in primary care; however, these rarely focus on near misses or the coordination of near-miss reports with quality improvement (QI). [2][3][4][5][6][7][8][9] Barriers to reporting events include the additional workload burden, concern over punitive action, lack of confidence that positive change will result, and psychological barriers to admitting an error. 10 -14 Anonymous reporting systems may increase the number of error reports and reduce concerns about punitive actions but might reduce the detail of the events.…”
mentioning
confidence: 99%
“…There was a balance in the yearly distribution of the articles' publication: four in 2007 9,10,11,12 , six in 2008 13,14,15,16,17,18 , three in 2009 19,20,21 , ten in 2010 22,23,24,25,26,27,28,29,30,31 , six in 2011 32,33,34,35,36,37 and four in 2012 38,39,40,41 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies used interviews to obtain data, either with physicians 25,33,39 or with physicians and other health professionals 24 . Questionnaires were also used by some authors to extract data, and were answered by physicians 22,40 , physicians and other health professionals 10,16,28,34 , or patients and family members 26,27 . Other studies used a combination of methods for data sources: incident reporting systems, direct observation, and focus groups 35 ; incident reporting systems, direct observation, and interviews 11 ; direct observation with audio recording 29 ; direct observation and expert consensus 36 ; incident reporting systems, patient file review, and interviews 41 ; incident reporting systems and patient file review 21 ; incident reporting systems, interviews, and questionnaires 30 ; expert consensus, questionnaires for patients, and focus groups 31 ; incident reporting systems, patient file review, and questionnaires 41 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations